The Moralization of the Undeserving Poor in Times of Crisis (KULT_online, 2020)
The book Moralising Poverty. The ‘Undeserving’ Poor in the Public Gaze by Serena Romano argues that the construction of moral boundaries between deserving and undeserving poor still shapes today’s institutions of redistribution such as welfare states. The book traces the origins of discourses about the ‘deservedness’ of social support in Western history and provides an analysis of current narratives about the allegedly undeserving poor. Romano’s main argument is that the moralization of the poor reappears in societies especially in times of crisis. Making an important contribution to the field of social policy by revealing normative orders and public narratives of ‘deservedness’, the broad study also sheds light on the moral basis of welfare states as well as social dynamics of inclusion, exclusion and solidarity.